IMPLEMENTASI PENDIDIKAN AKHLAK DALAM PEMBELAJARAN AL-QUR’AN HADIST DI LINGKUNGAN MAN 1 PEKALONGAN - Mailin Titi Hafsari_Adella Elsa putri (Al-Nizam: Indonesian Journal of Research and Community Service, 2024)
Moral education is the main foundation in character building of students, especially in the madrasah environment, especially in the modern era which is full of moral challenges. This study aims to explore the urgency of moral education, strategies for instilling noble morals through learning the Qur'an and Hadith, as well as the impacts and challenges faced at MAN 1 Pekalongan. The research method used is descriptive qualitative with a literature study approach. The results of the study indicate that moral education is very important in withstanding moral challenges in the modern era. Learning the Qur'an and Hadith at MAN 1 Pekalongan has been implemented through an integrative approach that combines spiritual values ​​with daily practices. However, challenges such as the negative influence of social media and the lack of role models in the surrounding environment are still obstacles. Synergy is needed between teachers, parents, and the community to optimize moral education in the school environment. However, challenges such as differences in students' educational backgrounds and lack of understanding of the texts of the Qur'an and Hadith are obstacles in the learning process. Therefore, contextual and interactive learning strategies are needed to overcome these challenges. Keywords: Implementation of Education, Moral Education, Al-Qur'an Hadith. Pendidikan akhlak merupakan fondasi utama dalam pembentukan karakter peserta didik, khususnya di lingkungan madrasah terutama di era modern yang penuh tantangan moral. Penelitian ini bertujuan untuk mengeksplorasi urgensi pendidikan akhlak, strategi penanaman akhlak mulia melalui pembelajaran Al-Qur’an Hadis, serta dampak dan tantangan yang dihadapi di MAN 1 Pekalongan. Metode penelitian yang digunakan adalah kualitatif deskriptif dengan pendekatan studi pustaka. Hasil penelitian menunjukkan bahwa pendidikan akhlak sangat penting dalam menghadapi tantangan moral di era modern. Pembelajaran Al-Qur’an dan Hadis di MAN 1 Pekalongan telah diterapkan melalui pendekatan integratif yang menggabungkan nilai-nilai spiritual dengan praktik keseharian. Namun, tantangan seperti pengaruh negatif media sosial dan kurangnya keteladanan di lingkungan sekitar masih menjadi hambatan. Diperlukan sinergi antara guru, orang tua, dan masyarakat untuk mengoptimalkan pendidikan akhlak di lingkungan sekolah Namun, tantangan seperti perbedaan latar belakang pendidikan siswa dan kurangnya pemahaman terhadap teks Al-Qur’an dan Hadis menjadi hambatan dalam proses pembelajaran. Oleh karena itu, diperlukan strategi pembelajaran yang kontekstual dan interaktif untuk mengatasi tantangan tersebut. Kata kunci: Implementasi Pendidikan, Pendidikan Akhlak, Al-Qur’an Hadist.